SUPERAÇÃO DE DORMÊNCIA DE SEMENTES DE ILEX PARAGUARIENSIS - PIRES, Valdirene da Silva,; SANTOS, Stephany,; OLIVEIRA, Manoel Garcia,; SILVA, Gabriel Ojeda,; MENDONÇA, Cristiane Gonçalves, (ANAIS DO ENIC, 2025)
-